A new species of the genus Protoplotina Miyatake (Coleoptera: Coccinellidae) from India - Poorani, J. (Zootaxa, 2003)
Protoplotina nigrosuturalis sp. n. and Protoplotina near vietnamica Miyatake are reported from India. This is the first record of this genus from India.